The Influence of Innovative Behavior and Growth Mindset on Work Productivity with Job Flourishing as a Moderator - Keradjaan, Herson (Journal of Entrepreneurship & Business, 2025)
Purpose: The study aims to examine the direct influence of innovative behavior, growth mindset, and job flourishing on work productivity, as well as the moderating impact of job flourishing on the influence of innovative behavior and the influence of growth mindset on work productivity. Method: The research sample is employees who have worked productively. The study employs a structural equation modeling approach, utilizing a moderated regression analysis method with Smart PLS. Results: The study's findings demonstrate that innovative behavior, a growth mindset, and job flourishing have a positive impact on work productivity. A flourishing job strengthens the influence of a growth mindset on work productivity. The implication is that to increase employee work productivity, the main strategy priority recommended by this study is to promote innovative behavior, the second priority is to implement a good growth mindset strategy, and the third priority is to adopt a strategy to enhance employee job flourishing. These three things are very effective in increasing work productivity. Another alternative to increase work productivity is to synergize strategies through collaboration with a growth mindset and job flourishing. Job flourishing can enhance the positive impact of a growth mindset on employee work productivity. By combining the growth mindset with job flourishing among employees, employee work productivity will also increase significantly.